In the Age of Synthetic Biology, Will Antimicrobial Peptides be the Next Generation of Antibiotics? - Félix Jaumaux; Luz P. Gómez de Cadiñanos; Philippe Gabant (MDPI AG, 2020)
Antibiotics have changed human health and revolutionised medical practice since the Second World War. Today, the use of antibiotics is increasingly limited by the rise of antimicrobial-resistant strains. Additionally, broad-spectrum antibiotic activity is not adapted to maintaining a balanced microbiome essential for human health. Targeted antimicrobials could overcome these two drawbacks. Although the rational design of targeted antimicrobial molecules presents a formidable challenge, in nature, targeted genetically encoded killing molecules are used by microbes in their natural ecosystems. The use of a synthetic biology approach allows the harnessing of these natural functions. In this commentary article we illustrate the potential of applying synthetic biology towards bacteriocins to design a new generation of antimicrobials.